Chronostratigraphy, mineralogy, susceptibility and inclination measurements of Quaternary sediment core samples from Lake Acigöl - François Demory; Claire Rambeau; Anne-Elisabeth Lebatard; Mireille Perrin; Syed Blawal; Valerie Andrieu-Ponel; Pierre Rochette; Hülya Alçiçek; Nicolas Boulbes; Didier L Bourlès; Cahit Helvaci; Rainer Petschick; et al. (PANGAEA, 2019)
A 601 m long sedimentary sequence was drilled in Lake Acigöl, located in the lakes region of SW Anatolia, near the Denizli travertine from which the oldest hominin of Turkey was unearthed. Among all dating methods applied to the sedimentary sequence, paleomagnetism, through the recognition of geomagnetic chrons, was the most successful and led to a quasi linear age model, with the 601 m long sedimentary record covering the last 2.3 Ma. An attempt to use the atmospherically deposited 10Be as a dating method was not very successful but provides interesting clues on this new method. Long-term lake level changes are depicted through lithological variations, in particular the carbonates and evaporites abundance. This change could be influenced by both long term cooling during the last 2 Ma and tectonic activity, which may in particular be responsible for a maximum water depth at around 1.8 Ma. Despite active tectonic influence, the sedimentary facies description and the magnetic susceptibility record (cleaned from tephra intervals) show that climate fluctuations (i.e., glacial-interglacial alternations) are likely recorded in the sedimentary succession, with warm periods marked by enhanced carbonate precipitation and cold and dry periods characterized by more detrital input linked to reduced vegetation cover and consequently more erosion in the catchment area. Preliminary pollen data, used to interpret magnetic susceptibility fluctuations, show that an average dry and open landscape prevailed around Acigöl lake during the whole record.
Supplement to: Demory, François; Rambeau, Claire; Lebatard, Anne-Elisabeth; Perrin, Mireille; Blawal, Syed; Andrieu-Ponel, Valerie; Rochette, Pierre; Alçiçek, Hülya; Boulbes, Nicolas; Bourlès, Didier L; Helvaci, Cahit; Petschick, Rainer; Mayda, Serdar; Moigne, Anne-Marie; Nomade, Sébastien; Ponel, Philippe; Vialet, Amélie; Alçiçek, Mehmet Cihat; Aumaître, Georges; Keddadouche, Karim (2020): Chronostratigraphy, depositional patterns and climatic imprints in Lake Acigöl (SW Anatolia) during the Quaternary. Quaternary Geochronology, 56, 101038, https://doi.org/10.1016/j.quageo.2019.101038